Circulating 27-hydroxycholesterol and breast cancer tissue expression of CYP27A1, CYP7B1, LXR-β, and ERβ: results from the EPIC-Heidelberg cohort - Le Cornet, Charlotte; Walter, Britta; Sookthai, Disorn; Johnson, Theron S.; Kühn, Tilman; Herpel, Esther; Kaaks, Rudolf; Turzanski Fortner, Renée (Breast cancer research, 2020)
Experimental and epidemiological studies demonstrate a role for 27-hydroxycholesterol (27HC) in breast cancer development, though results are conflicting. Cholesterol 27-hydroxylase (CYP27A1) and oxysterol 7-alpha-hydroxylase (CYP7B1) regulate 27HC concentrations, while differential expression of the liver X receptor (LXR) and estrogen receptor beta (ERβ) may impact the association between 27HC and breast cancer risk.
Gesehen am 08.04.2020